GOMES, Marcos Cardoso. (2016). A Ironia Trágica em Heródoto. Com prefácio de Jaa Torrano. 1ª ed. Curitiba: Editora Prismas, 325 p. (PHAINE: Revista de Estudos sobre Antiguidade, 2017)
GOMES, Marcos Cardoso. (2016). A Ironia Trágica em Heródoto. Com prefácio de Jaa Torrano. 1ª ed. Curitiba: Editora Prismas, 325 p.